تكييف سلم اختلال النشاط المعرفي - روبي, محمد لخضر; بوختالة, رياض (جامعة الوادي - University of Eloued, 2019)
هدفت الدراسة الحالية إلى محاولة تكييف سلم اختلال النشاط المعرفي لمايرس ورولين لدى طلاب الجامعة في البيئة الجزائرية، وذلك عن طريق إجراءات التكييف المتبعة وكذا التأكد من تطابق خصائصه السيكومترية (الثبات، الصدق، المعايير)، مع شروط الاختبار الجيد، وتم صياغة المشكلة في عدة تساؤلات . واستخدم الباحث المنهج الوصفي، وتكونت عينة الدراسة من( 496 ) طالب وطالبة يمثلون العينة الكلية للدراسة، تم استعمال الأساليب الإحصائية التالية : معامل ألفا كرونباخ (0.83) وطريقة كيودر ريدشارسون(21) (0.67) من أجل التحقق من الثبات، ومعامل الارتباط بين البند والدرجة الكلية، ومعامل الارتباط بين البند والبعد الذي ينتمي إليه، ومعامل الارتباط بين البعد والدرجة الكلية من أجل التحقق من صدق الاتساق الداخلي(0.81)، كما تم ايجاد معايير الأداء للسلم عن طريق استخراج المعايير الزائية والتائية. وقد توصلت الدراسة إلى النتائج التالية : -يتوفر سلم اختلال النشاط المعرفي على مؤشرات ثبات مقبولة وهذا ما أظهره معامل الثبات ألفا كرونباخ وطريقة كيودر ريدشارسون(21). -يتوفر سلم اختلال النشاط المعرفي على مؤشرات صدق مقبولة عبرت عنها مؤشرات الصدق من خلال ما أظهرته معاملات ارتباط صدق الاتساق الداخلي، وكذلك الصدق العاملي. -تتوفر في سلم اختلال النشاط المعرفي محكات معيارية من خلال الدرجات الزائية والتائية وفق التخصصات العلمية والأدبية لدى الطلبة.ABSTRACT:This study aimed at trying to adapt the scale of cognitive activity by Meyers and Rollin to the Algerian university students by means of the followed adaptive procedures and to also to ensure that its cycometric properties(stability, validity, standards) are consistent with the conditions of good testing. The problematic has been formulated in a set of questions. The descriptive method was adopted. The sample of the study consisted of )496) students(male and female). The following statistical methods were used: Alpha Kronbach)0.83( and Coder Richardson )0.67(to verify stability; whereas, for reliability the correlation coefficient between the item and the dimension to which it belongs was calculated, and the coefficient of correlation between the dimension and the total score in order to verify the validity of the internal consistency .(0.81)Performance criteria for the scale were also found. In addition to that, the validity of the question of gender differences in cognitive impairment was tested. The study ended with the following results: -The level of cognitive impairment is characterized by acceptable stability indicators. This is demonstrated by both the alpha-Cronbach stability coefficient and the method of Ciudar Richardson(21). -The level of cognitive impairment is characterized by acceptable indicators of reliability expressed by the indicators through what was shown by the correlation coefficients of the validity of internal consistency, as well as factor validity.
مقال
Keywords: تكييف، النشاط المعرفي; Adapt; cognitive activity